An intersectional reading of circular economy policies: towards just and sufficiency-driven sustainabilities. Issue 10 (2nd November 2022) - Rask, Nanna
ABSTRACT: Transitions to a circular economy (CE) have, in recent years, emerged as a popular approach to deal with the challenges related to the systemic crises of the Anthropocene. However, mainstream CE discourses have been critiqued for being ecomodernist and for focusing too much on managerial issues, at the expense of justice and social aspects, and thereby risking not leading to the systemic changes so direly needed. Given this backdrop, as well as cities key role in responding to sustainability challenges, this article adopts a posthumanist intersectionality-perspective to explore the transformative potential of a municipal policy in which CE has been adopted as a key strategy for achieving change. A critical policy analysis of the City of Gothenburg's new Environment and Climate Programme reveals that, apart from a focus on efficiency, the Programme also includes a politics of sufficiency and decreased consumption, thus potentially taking a first step within Swedish public sector towards an outspoken post-growth paradigm. The analysis, moreover, provides insights into what notions of citizens (or Gothenburgians), justice, responsibility, and nature–human relations the Programme is underpinned by. Drawing on these findings, the article proposes practical implications for urban policymakers and avenues for further research.